Effect of Hyperhomocysteinemia on Clinical Outcome and Hemorrhagic Transformation After Thrombolysis in Ischemic Stroke Patients - Luo, Yun; Jin, Hang; Guo, Zhen-Ni; Zhang, Peng; Zhang, Li-Yue; Chen, Jie; Yu, Yao; Wang, Yan; Liu, Jie; He, Qian-Yan; Sun, Xin; Yang, Yi (Frontiers in Neurology, 2019)
Background and Purpose: Hyperhomocysteinemia (Hhcy) is a well-known risk factor for ischemic stroke. However, the role of Hhcy in the clinical outcome of ischemic stroke has not been fully elucidated. In addition, previous studies have found that Hhcy was implicated in the disruption of the blood–brain barrier, which may increase the risk of hemorrhagic transformation (HT) after thrombolysis. Thus, the aim of this study was to investigate the effect of Hhcy on the clinical outcome and HT after thrombolysis in ischemic stroke patients. Methods: Patients who were diagnosed with ischemic stroke and received intravenous thrombolytic therapy between January 2016 and September 2018 were included in this study. Multivariate logistic regression analysis was used to assess the association between Hhcy, clinical outcome, and HT after thrombolysis. Furthermore, the potential interaction between Hhcy and hypertension on the clinical outcome and HT after thrombolysis was also assessed. Results: Of 568 patients, 455 (80.1%) had Hhcy, 66 (11.6%) had HT, and 219 (38.6%) had poor outcome. Patients with Hhcy had a higher incidence of poor outcome than the patients with non-Hhcy (40.9% vs. 29.2%, p=0.022). However, there was no significant difference in the incidence of HT (11.9% vs. 10.6%, p=0.711) between patients with Hhcy and non-Hhcy. After adjustment for major covariates, multivariate logistic regression analysis disclosed that Hhcy was independently associated with increased risk of poor outcome (OR=1.760; 95% CI: 1.069–2.896) but was not associated with the risk of HT (OR=1.017; 95% CI: 0.495–2.087). In addition, we found no significant interaction between Hhcy and hypertension on the clinical outcome (p=0.513) or HT (p=0.170) after thrombolysis. Conclusion: We found that Hhcy was an independent risk factor for poor outcome, but not an independent risk factor for HT after thrombolysis in ischemic stroke patients. In addition, there was no significant interaction of Hhcy and hypertension on the clinical outcome or HT after thrombolysis.